Waldenström macroglobulinemia: biology, genetics, and therapy - Paludo J (Dove Medical Press, 2016)
Jonas Paludo,1,2 Stephen M Ansell,1 1Division of Hematology, 2Division of Medical Oncology, Mayo Clinic, Rochester, MN, USA Abstract: Waldenström macroglobulinemia (WM) is a distinct clinicopathologic entity characterized by the presence of a lymphoplasmacytic lymphoma, a non-Hodgkin lymphoma, and IgM monoclonal gammopathy. WM is an indolent, uncommon malignancy mostly affecting the elderly. Patient outcomes have modestly improved since the introduction of rituximab to conventional cytotoxic chemotherapy more than 20 years ago. However, the pivotal discovery of the somatic MYD88 L265P mutation, harbored by most patients with WM, and the somatic CXCR4 WHIM mutations, similar to germline CXCR4 mutations seen in the warts, hypogammaglobulinemia, immunodeficiency, and myelokathexis (WHIM) syndrome, present in approximately one-third of patients with WM, has fundamentally changed our understanding of this disease and expanded the potential therapeutic targets. Within this new paradigm, ibrutinib emerged as a promising new drug. Ibrutinib targets Bruton’s tyrosine kinase, a downstream protein in the B-cell receptor pathway that is overactivated by the MYD88 L265P mutation. A seminal Phase II trial of ibrutinib in previously treated WM patients showed impressive response rates and confirmed the effects of MYD88 L265P and CXCR4 WHIM mutations in response to therapy. Ibrutinib is the first and only US Food and Drug Administration–approved drug specifically for the treatment of WM. However, before ibrutinib can be established as the standard of care for WM, long-term data regarding efficacy and safety are required. Further research to address ibrutinib resistance and cost-effectiveness is also imperative before ibrutinib can gain widespread acceptance. This review will cover the present pathophysiologic understanding of WM in light of the recent MYD88 and CXCR4 discovery, as well as current and emergent treatment regimens with focus on ibrutinib. Keywords: Bruton’s tyrosine kinase, ibrutinib, lymphoplasmacytic lymphoma, Waldenström macroglobulinemia